Find the product of:
(i) 2x, 5y and 7z                 (ii) 4xy, 5x2y2 and 6x3y3
Simplify the expressions and evaluate them as directed:
(i) x(x – 3) + 2 for x = 1 (ii) 3y(2y – 7) – 3(y – 4) – 63 for y = –2.
Multiply the binomials
(2.5l - 0. 5m) and (2.5l + 0.5m)
(2.5l - 0. 5m) x (2.5l + 0.5m)
                          = 2.5l(2.5l + 0.5m) - 0.5m) - 0.5m(2.5l + 0.5m)
                          = (2.5l x 2.5l) + (2.5l x 0.5m) - (2.5l x 0.5m) - (0.5m x 0.5m)
                          = 6.25l2 + 1.251m - 1.25lm - 0.25m2
                          = 6.25l2  - 0.25m2